Mini-open Lateral En Bloc Corpectomy: Cadaveric Feasibility and Early Clinical Experience. Issue 4 (May 2019) - Turner, Jay D.; Zaidi, Hasan A.; Godzik, Jakub; Albuquerque, Felipe C.; Uribe, Juan S.
Abstract : Background: Open approaches to the thoracolumbar spine for en bloc vertebral body tumor resection are associated with significant surgical morbidity. Less invasive surgical techniques may reduce complications. Objective: To present our experience with a staged posterior midline and mini-open anterolateral extracoelomic approach to en bloc corpectomy for vertebral body tumor resection in cadaver specimens and patients. Materials and Methods: The feasibility and safety of the staged posterior midline and mini-open anterolateral extracoelomic approach were evaluated in 3 cadaveric specimens. The procedure was performed at 3 levels (L1–L3) in each cadaver specimen (9 levels) and then in 1 clinical case. The cadaveric neurovascular structures were evaluated for tissue injury, whereas the operative experience, patient complications, and early surgical and clinical outcomes were reviewed. Results: The approach allowed for en bloc corpectomy without any injury to the cadaveric neurovascular structures. The procedure was reproducible in the clinical setting, which showed favorable clinical and radiographic patient outcomes. Conclusions: Early clinical experience suggests the staged posterior midline and mini-open anterolateral extracoelomic approach is feasible and safe for en bloc tumor resection compared with open techniques with related morbidity. Long-term studies are needed to understand the strengths and limitations of this technique. Abstract : Supplemental Digital Content is available in the text.